Efektifitas Senam Nifas Terhadap Involusi Uteri Pada Ibu Nifas Di BPM Siti Sujalmi Jatinom Klaten - Endang Wahyuningsih (Stikes Muhammadiyah Klaten, 2020)
Postpartum mothers will experience changes in uterine involution, namely the process of returning the uterus to its pre-pregnancy state. The uterus will experience a reduction in size in about 6 weeks. However, it can be faster if it is balanced with postpartum exercise. This study aims to determine the effectiveness of postpartum exercise on uterine involution in postpartum mothers at BPM Siti Sujalmi. This research method is Pre-Experimental Designs (Nondesigns) with a Pretest-Posttest group. The number of research samples were 24 respondents who were divided into two groups. Sampling with purposive sampling technique. The instrument used was the observation sheet. Data were analyzed using the Mann Whitney test. The results showed that uterine involution in post-partum mothers in the pretest intervention group was mostly fast as many as 7 respondents (58.3%) and the control group was mostly normal and slow respectively as many as 5 respondents (41.7%) while the posttest intervention group was mostly fast. as many as 7 respondents (58.3%) and the control group mostly normal and slow respectively as many as 5 respondents (41.7%). The conclusion of this study is that postpartum exercise is effective against uterine involution in postpartum mothers at BPM Siti Sujalmi, Jatinom with a p value of 0.021 (p <0.05). It is advisable for midwives to provide training through classes for pregnant women in the implementation of postpartum exercise to improve postpartum recovery or rapid uterine involution.